History of Alcohol Consumption and HIV Status Relate to Functional Connectivity Differences in the Brain During Working Memory Performance - Bryant, Vaughn (Curr HIV Res, 2020)
BACKGROUND: Poorer working memory function has previously been associated with alcohol misuse, Human Immunodeficiency Virus (HIV) positive status, and risky behavior. Poorer working memory performance relates to alterations in specific brain networks. OBJECTIVE: The current study examined if there was a relationship between networks involved in working memory and reported level of alcohol consumption during an individual’s period of heaviest use. Furthermore, we examined whether HIV status and the interaction between HIV and alcohol consumption was associated with differences in these brain networks. METHOD: Fifty adults, 26 of whom were HIV positive, engaged in an n-back working memory task (0-back and 2-back trials) administered in a magnetic resonance imaging (MRI) scanner. The Kreek-McHugh-Schluger-Kellogg (KMSK) scale of alcohol consumption was used to characterize an individual’s period of heaviest use and correlates well with their risk for alcohol dependence. Connectivity analyses were conducted using data collected during n-back task. RESULTS: Functional connectivity differences associated with greater alcohol consumption included negative connectivity, primarily from parietal attention networks to frontal networks. Greater alcohol consumption was also associated with positive connectivity from working memory nodes to the precuneus and paracingulate. HIV positive status was associated with more nodes of negative functional connectivity relative to alcohol consumption history alone, particularly in the fronto-parietal networks. The HIV positive individuals with heavier drinking history related to negative fronto-parietal connectivity, along with positive connectivity from working memory nodes to mesolimbic regions. CONCLUSION: Findings allow for a better understanding of brain networks affected by HIV and alcohol and may provide avenues for interventions.